Model Pembelajaran Discovery Learning pada Pembelajaran Agribisnis Tanaman dalam Mengukur Kemampuan Berpikir Kritis Peserta Didik - Amalia, Rizky; Rachmawati, Rivanna Citraning; Wardani, Susilo (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
Critical thinking skills are one of the essential 21st-century skills to support students in facing the increasingly complex challenges of the workforce. However, vocational education often focuses on mastering technical competencies, which leads to the neglect of critical thinking skill development. The discovery learning model enables students to construct independent knowledge through active and meaningful learning experiences. This study aims to analyze the level of critical thinking skills of Agribusiness Crop and Horticulture (ATPH) students at SMK Negeri 1 Bawen during agribusiness learning using the discovery learning model. The research was conducted in class XI ATPH B using a descriptive quantitative method. Data were collected through student worksheets and observation sheets, which were analyzed based on critical thinking indicators, including interpretation, analysis, evaluation, conclusion drawing, explanation, and self-regulation. The results showed that the student's critical thinking skills were categorized as good, with an average score of 65.91. However, the indicators of analysis and explanation were rated as sufficient, indicating the need for greater integration of critical thinking-based learning models into educational activities.